Extracranial arteries of the dog - Hasan Erden; Nejdet Dursun; İsmail Türkmenoğlu (Eurasian Journal of Veterinary Sciences)
In this study was undertaken to determine the arterial vascularisation of the head of Turkish shepherd dog. As a material, fourteen adult dogs were used. The external carotid artery that the main source of the blood supply to the head of the dog has been determinated by means of coloured latex injected through the common carotid artery.